Under Jerusalem the buried history of the world's most contested city - Lawler, Andrew 1961- (New York Doubleday, 2021)
A Moment of Insanity -- A Fool's Errand -- A Masonic Mission -- The Roots of Our Problem -- A Faithful Watchman -- A Great and Potent Force -- Gone with the Treasures of Solomon -- A Dangerous Fantasy -- Exalting the Walls -- The Magnificence of the Metropolis -- The Rabbi's McGuffin -- Someone of Great Imagination -- A Free People In Our Land -- The Cellar Crusade -- The Bedrock of Our Existence -- Millennial Madness -- Ruins in the Mind -- Reality is Always Stronger Than Belief -- The Rebel Dig -- Resistance by Existence -- Here We Will Stay -- Return of the Queen.
"A sweeping history of Jerusalem and the pivotal role that archaeology has played--both in its invention as a modern holy city and as the match that lit a geopolitical fire beneath it In 1863, a French politician and adventurer heard a rumor of biblical treasures beneath Jerusalem. At the time, Jerusalem was a venerable backwater, not the thriving religious center we think of today. Archaeology itself was in its infancy--more a pastime for treasure-hunting aristocrats than a legitimate scientific discipline. But when Louis-Felicien Joseph Caignart De Saulcy dug into the desert and discovered an ancient tomb, explorers from England, Germany, and Russia followed in his footsteps, competing with one another to make the next big find. De Saulcy's dig gave rise not only to a new field; it opened a Pandora's Box, turning Jerusalem into the most disputed piece of land on Earth. Under Jerusalem is a 150-year history of the ground just beneath one of the world's holiest cities. It examines the way that archaeology has not only fueled academic disputes but has contributed to some of the bloodiest chapters in Israel's modern history. With an eye on both the past and the future, Andrew Lawler reveals how more than a century of researchers, propelled as much by nationalist agendas as any thirst for knowledge, sparked a revolution in the Middle East, one whose reverberations we continue to feel"--
Includes bibliographical references and index
Keywords: Excavations (archaeology) -- Jerusalem; Jerusalem -- History; Jerusalem -- Antiquities